Tanggung Jawab Notaris Atas Karya Yang Tidak Menerapkan Prinsip Kehati-Hatian (Studi tentang Gugatan Pembatalan Akta Pada Putusan Mahkamah Agung Nomor 3390 K/Pdt/2015) - Sekar Ayu Amiluhur Priaji (Officium Notarium, 2022)
This research aims to analyze the "Responsibilities of Notary for Deeds that Fails to Apply the Prudentiality Principle (Study of Lawsuit for Cancellation of Deeds in Supreme Court Decision Number 3390 K/Pdt/2015)", with the following problem formulation: First, what is the basis the legal considerations of the panel of judges annulled the Notary Deed in the Supreme Court Decision Number 3390 K/Pdt/2015; Second, what is the responsibility of the Notary for a deed that fails to apply the precautionary principle. This is a normative juridical research. The research data was obtained by means of literature and document studies. The analysis used in this research is juridical analysis. The results of this study conclude that, first: canceling the notarial deed in the Supreme Court Decision Number 3390 K/Pdt/2015, is the basis for making a grant deed with a power of attorney which legally and legally is null and void so that the agreement is deemed not to exist or has never been born, second: the form The responsibility of the notary for a deed made without applying the precautionary principle is a moral responsibility, however, if the error occurs due to the negligence of the notary and results in losses by the parties, then legal remedies can be taken to hold the notary accountable in making an authentic deed.Key Word: Precautionary principle, deed, notary AbstrakPenelitian tesis ini bertujuan untuk menganalisis “tanggung jawab Notaris atas akta yang tidak menerapkan prinsip kehatian-hatian (Studi tentang gugatan pembatalan akta pada putusan Mahkamah Agung Nomor 3390 K/Pdt/2015)”,dengan rumusan masalah, pertama, apa yang menjadi dasar pertimbangan hukum majelis hakim membatalkan Akta Notaris pada Putusan Mahkamah Agung Nomor 3390 K/Pdt/2015, Kedua, bagaimana tanggung jawab Notaris atas akta yang tidak menerapkan prinsip kehati-hatian. Penelitian ini merupakan penelitian Yuridis Normatif. Data penelitian diperoleh dengan cara studi pustaka dan dokumen. Analisis yang digunakan dalam penelitian ini adalah analisis yuridis. Hasil penelitian ini menyimpulkan, pertama, membatalkan akta notaris pada Putusan Mahkamah Agung Nomor 3390 K/Pdt/2015, adalah dasar pembuatan akta hibah dengan surat kuasa dimana secara yuridis logis batal demi hukumsehingga perikatan itu dianggap tidak ada atau tidak pernah lahir, kedua, bentuk pertanggung jawaban notaris terhadap akta yang dibuat tanpa menerapkan prinsip kehati-hatian merupakan tanggung jawab moral, namun demikian apabila kesalahan tersebut terjadi karena kelalaian notaris dan mengakibatkan kerugian oleh para pihak, maka dapat dilakukan upaya hukum dalam meminta pertanggung jawaban notaris dalam membuat sebuah akta otentik.Kata-kata Kunci: Prinsip kehati-hatian, Akta, Notaris